Serum norethisterone (NET) levels in NET-enanthate (NET-EN) injectable contraception users substantially interfere with testosterone immunoassay measurements and confound interpretation of biological outcomes - Chanel Avenant; Johnson Mosoko Moliki; Alexis J. Bick; Sigcinile Dlamini; Mandisa Singata-Madliki; G. Justus Hofmeyr; Pai-Lien Chen; Karl-Heinz Storbeck; Donita J. Africander; David W. Erikson; Janet P. Hapgood (Contraception and Reproductive Medicine)
Abstract Background The progestin norethisterone (NET), which is structurally related to testosterone, and its enanthate form (NET-EN), are used in contraception in women. Oral NET has been shown to interfere with testosterone measurements by some chemiluminescence microparticle immunoassays (CMIA). However, whether serum NET in NET-EN users interferes with these assays is unknown. Methods Serum samples were obtained from women randomized to the injectable contraceptives NET-EN or depo medroxyprogesterone acetate intramuscular (DMPA-IM) in a clinical trial conducted in South Africa. Testosterone concentrations were compared after measurement by Abbott Architect CMIA and ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS), from matched samples collected at baseline (D0) and 25 weeks (25W) after initiation. Results At 25W, testosterone concentrations in the NET-EN arm were significantly higher (271%) using the CMIA compared to the UHPLC-MS/MS method. Contrary to the UHPLC-MS/MS results showing a significant decrease in testosterone concentrations in the NET-EN arm from D0 to 25W, a significant increase was determined by CMIA. Conversely, in the DMPA-IM arm at 25W, no significant difference in testosterone concentrations between the two methods was detected, and both methods showed a significant decrease in testosterone from D0 to 25W. Conclusions We show for the first time that physiological concentrations of NET in premenopausal NET-EN users interfere with testosterone quantification using a CMIA method. The degree of interference is much higher and occurs at lower concentrations of NET than has previously been reported for oral NET and confounds the biological outcome of NET-EN use on testosterone concentrations, individually and relative to DMPA-IM. Trial registration The WHICH trial was retrospectively registered with the Pan African Clinical Trials Registry (PACTR 202009758229976).